Bhojpuri work songs: Gender, genre and work spaces through embodiment performances - Rai, Dr. Ruchika (Yayasan Mitra Persada Nusantara, 2024)
This paper explores the connection between gender, genre, and work space through Bhojpuri work songs. These songs are an important cultural and social memory of the Bhojpuri society, representing the experiences, ideologies, and way of life of individuals. The performance of these songs is gendered, with men performing them in outside spaces and women performing them within households or in the fields. This gendering of performance spaces corresponds to the division of labour, with women assigned to household activities and men to activities in the outside world. The songs touch on various themes such as familial issues, fulfilling duties, complaints, celebration of relationships, accepting and hiding sexual desires, excitement and dedication while performing the labour; and even political issues. What distinguishes these songs is their coordination with the performance and with the work, which follows a specific beat and rhythm. They are nested performances that highlight the actions being performed. They follow a stylized pattern which is materialized and internalized through transgenerational memory, that are expressed through embodied enactment. Based on memory and embodied performances these work songs reject the surrogate bodies of the museumization and sustain themselves in an organic way.